Achieving sustainable food industries: good practices in environmental management - Abd. Manan, Fazilah (2006)
Historically, development strategies ignored the effect of economic activity on the environment. Few decades ago also have been marked by intensification of pollution. Then only people start to be aware on the importance of environmental preservation. Economic activities related to food manufacturing industries are one of the sources that contribute to unhealthy environment if the management within the industries is not carried out properly. This study is aimed to evaluate the level of environmental management system (EMS) within the food manufacturers in Johor. Their roles towards achieving sustainable environmental management are evaluated by questionnaire surveying method. The data were processed to obtain statistical results using SPSS 11.0 for Windows. A total of 200 sets of survey component were sent to the food manufacturers and the replies were 25 (12.5%). The results are mainly on awareness level, environmental management system applied and problems encountered towards achieving sustainable development. The awareness towards environmental criteria is in a fair condition. In terms of environmental practices, the relative index (RI) obtained for waste segregation; reduce, recycle and reuse activity; and landfill disposal of solid waste is 0.78. This indicates that the three approaches often being applied by them. Other waste management approaches including storage of waste on and off-site; direct discharge of waste into watercourse, drains or sewers; open land discharge; and incineration on or off-site is rarely applied, as the RI is only 0.26. The RI for wastewater management and air pollution control is 0.38 and 0.47 respectively. In conclusion, the awareness among them towards sustainable development is still below the satisfied level. However, the effort towards this objective is clearly shown through management practices applied, together with the earnest in complying to the rules and regulations. Although there are some difficulties traced, those can be overcome by full commitment between all parties involved